Accelerating high school students' science career trajectories through non-formal science volunteer programs. Issue 1 (2nd January 2023) - Rende, K.; Jones, M. Gail; Refvem, Emma; Carrier, Sarah J.; Ennes, Megan
ABSTRACT : Extensive research shows that non-formal science education programs effectively build and sustain long-term interest and persistence in science careers. Framed by expectancy-value theory, this study examined the academic and career outcomes of students who participated in a multi-year volunteer program at a science museum. Twenty-one participants were interviewed about their motivations for volunteering and the impact of participation on their science career trajectories. Data were coded for factors related to expectancy-value including goals, motivations, previous non-formal science experiences, and family attitudes towards science and STEM. Results showed participants of the volunteer program pursued science careers at higher rates than the national average, adding evidence to show how non-formal science education programs extend the longevity of science career interests. This study also documented a newly emergent phenomenon of acceleration of participant science career trajectories. Museum volunteer programs such as the one studied may help high school students gain knowledge and skills central to science career development earlier than is typical. The implications of this type of program for students with already established science interests and science career motivations is discussed from an equity perspective.